Rapid one-step real-time RT-PCR assay for the detection and quantitation of bluetongue virus - CHAND, KARAM; BISWAS, SANCHAY KUMAR; RAMAKRISHNAN, MUTHANNAN ANDAVAR (The Indian Journal of Animal Sciences, 2019)
Bluetongue virus (BTV) infects domestic and wild ruminants, but it is primarily a disease of sheep. In the present study, a rapid one-step real-time RT-PCR (RT-qPCR) assay based on SYBR green chemistry was optimized by targeting the conserved region of genome segment-10 (encoding NS3). The assay was able to detect BTV-1, 2, 9, 10, 16, 21 and 23 serotypes. The sensitivity of the assay using the RNA transcribed in vitro was 102 copies with 94.25%, efficiency. The sensitivity of the assay was compared to sandwich-ELISA (s-ELISA) and RT-PCR. The sensitivity of s-ELISA, RT-PCR and one step RT-qPCR for detection of BTV-1 was equivalent to 102.4 TCID50/ml, 100.4 TCID50/ml and 100.04 TCID50/ml, respectively and the assay was specific to BTV. Further, the assay was validated with whole blood samples from sheep and goats used to evaluate the assay performance. The assay provides an important tool for early and rapid detection of all serotype of BTV.